Long non-coding RNAs and splicing - Staněk, David (Essays in Biochemistry, 2021)
In this review I focus on the role of splicing in long non-coding RNA (lncRNA) life. First, I summarize differences between the splicing efficiency of protein-coding genes and lncRNAs and discuss why non-coding RNAs are spliced less efficiently. In the second half of the review, I speculate why splice sites are the most conserved sequences in lncRNAs and what additional roles could splicing play in lncRNA metabolism. I discuss the hypothesis that the splicing machinery can, besides its dominant role in intron removal and exon joining, protect cells from undesired transcripts.
Keywords: RNA, Long Noncoding; sestřih RNA; RNA dlouhá nekódující; RNA Splicing